The Effectiveness of Plyometric and Tabata on Leg Muscle Power and Anaerobic Endurance of Junior Volleyball Players of Panji Laras Club Nganjuk Regency - Syechalam Prabu Tunggul Jati; Nasuka; Sri Sumartiningsih (Universitas Negeri Semarang, 2025)
This study aimed to examine the effects of plyometric and Tabata training on leg power and anaerobic endurance in junior volleyball athletes from the Panji Laras Club, taking into account differences in leg length. A quasi-experimental design with a pretest–posttest structure was used, involving four groups: Plyometric A (long legs), Plyometric B (short legs), Tabata A (long legs), and Tabata B (short legs), each consisting of four athletes. Leg power was assessed using the vertical jump test, while anaerobic endurance was measured through the fatigue index. Both training programs were applied over the intervention period. The results showed that all groups experienced an increase in leg power, with improvements ranging from +2.25 to +3.50, and a decrease in fatigue index values, indicating better anaerobic endurance. Repeated-measures ANOVA revealed a significant main effect of time for both leg power (p < 0.001) and anaerobic endurance (p < 0.001), while no significant interaction effects were found between training type and leg length. These findings indicate that both plyometric and Tabata training effectively improved performance outcomes, and leg-length differences did not significantly influence adaptation. In conclusion, plyometric and Tabata training can be used as alternative methods to enhance leg power and anaerobic endurance in junior volleyball athletes.